Learning Training based on Digital Class Platform Edmodo for Teachers Al-Irsyad Islamic Junior High School - Endang Sulistianingsih; Sanday Jamaludin (ASEAN Journal of Empowering Community, 2021)
The problem facing partners is that the community has been hit by COVID-19, which resulted in learning in schools that were supposed to be held face-to-face become online or over distance. Tegal city has undergone a Lock-down period for 3 months, namely from March to May 2020. This makes all activities, especially academic fields, conducted through home orWorkFromHome (WFH). Learning activities are carried out remotely using several learning applications. Tegal City Education Office policy requiring all students in Tegal city to study remotely / online is one of the efforts to respond to the COVID-19 pandemic that hit Tegal City. This condition makes Al-Irsyad Islamic School (Mitra) Junior High School, in collaboration with ups Tegal Devotion Team, provide training toUstadz andUstadzahatau teachers who study in school trad in the technical matters of distance learning or online. There are several applications offered, such as Google Classroom, Quipper, Microsoft Teams, etc. Partners and the Devotion Team finally agreed that the appliance used was Edmodo because it was more quota friendly and connected features with parents. The result of this training is that all trainees already have an Edmodo account and have been able to react to it in the activities of learning online.